Analysis of Intonation: the Case of MAE_ToBI. Issue 1 (30th June 2016) - Gussenhoven, Carlos
Abstract : Annotation systems for intonation contours are ideally based on a well-motivated phonological analysis of the language in question, such that instances of indecision are restricted to uncertainties over what intonational structure the speaker has used, rather than over the choice of label in situations where no suitably distinctive label is available or more than one suitable label is available. This contribution inventorizes a number of cases of overanalysis and underanalysis in MAE_ToBI and argues that they are in large part due to the decision by Pierrehumbert (1980 ) to analyze a rising-falling accent as a rising pitch accent (L+H*) followed by a L-tone from a different source (an 'on-ramp' analysis). It is shown how the opposite choice, a falling pitch accent preceded by a L-tone from a different source (an 'off-ramp' analysis), avoids most of these problems. Results from a perception experiment testing MAE_ToBI's prediction of intonational boundaries show that steep falls do not always signal a boundary. The inclusion of a tritonal prenuclear pitch accent, which explains the absence of an intonational boundary after a steep fall followed by a gradual rise, can readily be accommodated in the 'off-ramp' analysis, but not in MAE_ToBI.